Charge transfer magnetoexcitons in magnetoabsorption spectra of asymmetric type-II double quantum wells - Röder, J.; Gerhard, M.; Fuchs, C.; Stolz, W.; Heimbrodt, W.; Koch, M.; Ngo, C.; Steiner, J. T.; Meier, Torsten (Physical Review B)

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.

Structural and Electrochemical Properties of F-Doped RbTiOPO4 (RTP:F) Predicted from First Principles - Bocchini, Adriana; Xie, Yingjie; Schmidt, Wolf Gero; Gerstmann, Uwe (Crystals)
Batteries based on heavier alkali ions are considered promising candidates to substitute for current Li-based technologies. In this theoretical study, we characterize the structural properties of a novel material, i.e., F-doped RbTiOPO4 (RbTiPO4F, RTP:F), and discuss aspects of its electrochemical performance in Rb-ion batteries (RIBs) using density functional theory (DFT). According to our calculations, RTP:F is expected to retain the so-called KTiOPO4 (KTP)-type structure, with lattice parameters of 13.236 Å, 6.616 Å, and 10.945 Å. Due to the doping with F, the crystal features eight extra electrons per unit cell, whereby each of these electrons is trapped by one of the surrounding Ti atoms in the cell. Notably, the ground state of the system corresponds to a ferromagnetic spin configuration (i.e., S=4). The deintercalation of Rb leads to the oxidation of the Ti atoms in the cell (i.e., from Ti3+ to Ti4+) and to reduced magnetic moments. The material promises interesting electrochemical properties for the cathode: rather high average voltages above 2.8 V and modest volume shrinkages below 13% even in the fully deintercalated case are predicted.

How to suppress radiative losses in high-contrast integrated Bragg gratings - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Journal of the Optical Society of America B)
High-contrast slab waveguide Bragg gratings with 1D periodicity are investigated. For specific oblique excitation by semi-guided waves at sufficiently high angles of incidence, the idealized structures do not exhibit any radiative losses, such that reflectance and transmittance for the single port mode add strictly up to one. We consider a series of symmetric, fully and partly etched finite gratings, for parameters found in integrated silicon photonics. These can act as spectral filters with a reasonably flattop response. Apodization can lead to more box shaped reflectance and transmittance spectra. Together with a narrowband Fabry–Perot filter, these configurations are characterized by reflection bands, or transmittance peaks, with widths that span three orders of magnitude.
Keywords: tet_topic_waveguide

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Entanglement of particles versus entanglement of fields: Independent quantum resources - Sperling, Jan; Agudelo, Elizabeth (Physical Review A)

Detector entanglement: Quasidistributions for Bell-state measurements - Sperling, Jan; Gianani, Ilaria; Barbieri, Marco; Agudelo, Elizabeth (Physical Review A)

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Efficient Modeling and Tailoring of Nonlinear Wavefronts in Dielectric Metasurfaces - Hähnel, David; Förstner, Jens; Myroshnychenko, Viktor (ACS Photonics)
Dielectric metasurfaces provide a unique platform for efficient harmonic generation and optical wavefront manipulation at the nanoscale. Tailoring phase and amplitude of a nonlinearly generated wave with a high emission efficiency using resonance-based metasurfaces is a challenging task that often requires state-of-the-art numerical methods. Here, we propose a simple yet effective approach combining a sampling method with a Monte Carlo approach to design the third-harmonic wavefront generated by all-dielectric metasurfaces composed of elliptical silicon nanodisks. Using this approach, we theoretically demonstrate the full nonlinear 2π phase control with a uniform and highest possible amplitude in the considered parameter space, allowing us to design metasurfaces operating as third harmonic beam deflectors capable of steering light into a desired direction with high emission efficiency. The TH beam deflection with a record calculated average conversion efficiency of 1.2 × 10–1 W–2 is achieved. We anticipate that the proposed approach will be widely applied as alternative to commonly used optimization algorithms with higher complexity and implementation effort for the design of metasurfaces with other holographic functionalities.
Keywords: tet_topic_meta

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Dispersion control with integrated plasmonic metasurfaces - Geromel, René; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (CLEO: Fundamental Science 2023)
We present a miniaturized pulse shaping device that creates an arbitrary dispersion through the interaction of multiple metasurfaces on less than 2 mm 3 volume. For this, a metalens and a grating-metasurface between two silver mirrors are fabricated. The grating contains further phase information to achieve the device's pulse shaping functionality.

Symmetry governed nonlinear selection rules in nanophotonics - Zentgraf, Thomas; Sain, Basudeb; Zhang, Shuang (Fundamentals and Applications of Nonlinear Nanophotonics)

Tailoring the directive nature of optical waveguide antennas - Farheen, Henna; Yan, Lok-Yee; Leuteritz, Till; Qiao, Siqi; Spreyer, Florian; Schlickriede, Christian; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Zentgraf, Thomas; Linden, Stefan; Myroshnychenko, Viktor; et al. (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate the numerical and experimental realization of optimized optical traveling-wave antennas made of low-loss dielectric materials. These antennas exhibit highly directive radiation patterns and our studies reveal that this nature comes from two dominant guided TE modes excited in the waveguide-like director of the antenna, in addition to the leaky modes. The optimized antennas possess a broadband nature and have a nearunity radiation efficiency at an operational wavelength of 780 nm. Compared to the previously studied plasmonic antennas for photon emission, our all-dielectric approach demonstrates a new class of highly directional, low-loss, and broadband optical antennas.
Keywords: tet_topic_opticalantenna